(untitled) (The Research of Medical Science Review, 2025)
Objective: To assess the knowledge and practices of pregnant women regarding supplementation of folic acid, iron, and calcium Methodology: This cross-sectional descriptive study was conducted at Jinnah Postgraduate Medical Center, Karachi, for a period of 6 months from June 05 to November 08, 2019. The study was carried out at the Outpatient Department of Gynaecology and Obstetrics. The calculated sample size of this study was 380 pregnant women. A self-administered study questionnaire was used for this study. Collected data was entered and analyzed by the Statistical Package for Social Sciences version 20. Frequency and percentage were calculated for categorical variables. Results: Out of 380 women, 138 (36.3%) had enough knowledge about folic acid, and 91 (24%) out of all respondents took folic acid during the preconception period. Regarding iron, 137 (36.1%) of respondents were aware of the uses of iron supplements, and only 211 (55.5%) of these respondents were taking iron supplements. Regarding calcium supplements, only 121 (31.8%) knew about it, and out of 380 women, only 149 (39.2%) were taking calcium during pregnancy. Overall, poor knowledge and practices of pregnant women were observed regarding supplements. Conclusion: Poor knowledge and inappropriate practices of pregnant women regarding the supplementation of folic acid, iron, and calcium demand from healthcare experts to arrange educational programs on adequate nutritional supplements during pregnancy for enhancing the knowledge and practices of pregnant women.